DEVELOPMENT DIRECTIONS FOR COMPETITIVE INDUSTRIAL SECTORS IN THE CONTEXT OF INTEGRATION INTO GLOBAL VALUE CHAINS - Farmonova Maftuna Norpulat qizi, (TADQIQOTLAR, 2026)
Abstract This  article  examines  the  development  directions  for  competitive  industrial sectors in the context of integration into global value chains, using Uzbekistan as a case study. The research evaluates industrial competitiveness through production capacity, manufacturing  structure,  investment  activity,  export  potential,  technological modernization,  import  dependence,  and  the  ability  of  industrial  enterprises  to participate in international production networks. The study applies dynamic analysis, structural analysis, comparative analysis, and criteria-based  assessment.  The  results  show  that  Uzbekistan’s  industrial  sector  has demonstrated stable growth in recent years. In 2025, industrial output reached 1,101.1 trillion soums, while the physical volume index of industrial production amounted to 106.8%. Manufacturing accounted for 947.2 trillion soums, or 86.0% of total industrial output. However, the persistence of a negative foreign trade balance and the high role of imported machinery and technological equipment indicate the need to strengthen industrial competitiveness through deeper integration into global value chains. The  article  proposes  several  development  directions,  including  technological modernization, export diversification, development of high value-added production, improvement of product quality, expansion of industrial clusters, integration of small and medium-sized enterprises into value chains, and increasing the effectiveness of investment projects.